Towards an appropriate regulatory environment for special economic zones in Nigeria - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
This study set out to examine the regulatory framework of the underperformed SEZ structure in Nigeria with the aim of identifying the factors that precluded it from achieving its objectives and hindering its competitiveness in the global market. The main question to be addressed is what regulatory deficits are in the implementation of SEZ programme in Nigeria that have precluded it from achieving its objectives. In approaching this question, this study examined the rationale underlying SEZ initiatives globally and the policy considerations for implementing sustainable SEZ. The study found that these policy components include strategic planning, comprehensive legal and regulatory framework, policy considerations, effective institutional framework, incentive framework, and physical development and management. The study further examined the regulatory framework underpinning SEZ development in Nigeria against the backdrop of the policy considerations identified. Using China's experience as benchmarks for successful SEZ development, the study draws lessons that could be useful in enhancing the competitiveness of the Nigerian zone programme. Moreover the study argues that weak regulatory environment is largely responsible for the underperformance of SEZ programmes in Nigeria in delivering its objectives. Specifically, the study made the following findings: ? Weak institutional and regulatory structures, infrastructural shortage, lack of linkages to the wider economy and policy instability are some of the challenges of SEZs in Nigeria. ? The study found that there is swiftness on the part of the government to create zones suggests that the government views SEZs as catalyst for economic diversification and industrialization. However, further evidence shows that the regulatory framework underlying the existing zone programme is not only weak but limited in scope to drive competitiveness. It also appears that the government has not been actively committed in the zone programme. The inference drawn here is that the Nigerian government does not actively see SEZ programme as part of its development strategy. ? The Nigeria zone regulatory framework needs a comprehensive restructuring with a view to improving the competitiveness of the zones. Concerted efforts could still be made to enhance the performance of the zones by strengthening the regulator to make it responsive to its responsibilities and engaging policies The research therefore concludes that engaging the instrumentality of SEZs as an engine of economic growth and industrial transformation will only be successful where the regulatory environment is favourable, attractive and competitive. Against the background of these findings, the study recommends that the starting point is for the government to adopt SEZ programme as part of its development strategy. The study also propose that adopting a comprehensive regulatory framework that will strengthening the institutional capacity of the regulator, give clarity to roles of the different stakeholders involved in SEZ development, support dynamic policies, constant policy reform and incorporate modern practices in the SEZ framework can jumpstart the competitiveness of the Nigeria zones.